2022
DOI: 10.3390/ijms232214436
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling in Metastatic Colorectal Cancer (mCRC): From Underlying Mechanism to Potential Applications in Clinical Development

Abstract: Colorectal cancer (CRC) is a serious public health issue, and it has the leading incidence and mortality among malignant tumors worldwide. CRC patients with metastasis in the liver, lung or other distant sites always have poor prognosis. Thus, there is an urgent need to discover the underlying mechanisms of metastatic colorectal cancer (mCRC) and to develop optimal therapy for mCRC. Transforming growth factor-β (TGF-β) signaling plays a significant role in various physiologic and pathologic processes, and aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 232 publications
0
10
0
Order By: Relevance
“…These differences might reflect the more nuanced and paradoxical role of TGF-β signaling in cancer, where it can be tumor suppressive and tumor promoting in the same tumor type at different stages of tumorigenesis. 57 …”
Section: Resultsmentioning
confidence: 99%
“…These differences might reflect the more nuanced and paradoxical role of TGF-β signaling in cancer, where it can be tumor suppressive and tumor promoting in the same tumor type at different stages of tumorigenesis. 57 …”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that TGF‐β is highly expressed in CRC, increasing the production of several mitotic growth factors, including TGF‐α, FGF, and EGF. Thus it acts as a tumor promoter in the final stages of CRC 50,51 . Angiogenesis is the development of new blood vessels that are involved in the genesis, growth, and metastasis of tumors and involves a variety of factors, including VEGF 52 .…”
Section: Discussionmentioning
confidence: 99%
“…49 The initiation of TGF-β signaling occurs through the binding of the a tumor promoter in the final stages of CRC. 50,51 Angiogenesis is the development of new blood vessels that are involved in the genesis, growth, and metastasis of tumors and involves a variety of factors, including VEGF. 52 VEGF levels and VEGFR activity are enhanced and associated with poor prognosis in CRC.…”
Section: Chrdl1 Inhibits Angiogenesis and Liver Metastasis Of Crc Cel...mentioning
confidence: 99%
“…The TGF-β signaling pathway is critical in many biological processes. It regulates cell growth, differentiation, apoptosis, cell motility, extracellular matrix production, epithelial–mesenchymal transition (EMT), angiogenesis, and cellular immunity [ 97 , 98 , 99 ]. There are three receptors in the TGF-β signaling pathway: Transforming growth factor-β receptor (TGFBR)-1, TGFBR2, and TGFBR3, and three ligand isoforms: TGF-β1, TGF-β2, and TGF-β3 [ 100 , 101 ].…”
Section: The Role Of the Signaling Pathways In The Carcinogenesis Of Crcmentioning
confidence: 99%
“…The deregulation of this pathway is associated with many diseases, such as cancer [ 103 ]. Indeed, the aberrant activation of this signaling pathway promotes a variety of tumors, including hepatocellular carcinoma, pancreatic cancer, esophageal cancer, gastric cancer and CRC [ 99 , 104 ]. In tumor, the TGF-β signaling pathway exhibits a paradoxical role that is known as the “TGF-β paradox” [ 97 ] ( Figure 6 ).…”
Section: The Role Of the Signaling Pathways In The Carcinogenesis Of Crcmentioning
confidence: 99%